Population Pharmacokinetics of Rifampicin on Pulmonary Tuberculosis Patients - Son Nhat, Bui; Dinh Hoa, Vu; Anh Tuan, Le; Thi Luyen, Le (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2019)
Abstract: This study aimed to establish a reasonable population pharmacokinetic model for rifampicin taken orally by patients with pulmonary tuberculosis, estimate pharmacokinetic parameters as well as influencing covariates. Blood samples of patients were collected at day 10 – 14 after commencing treatment. Time – concentration data were handled using non-linear mixed-effect model with Monolix 2018. An one-compartment, linear elimination, absorption with transit compartments model was found to be the most suitable for rifampicin. Volume of distribution (33,5 L) and clearance (9,62 L) were found to be influenced by fat-free mass (calculated using Janmahasatian’s method). Absorption-related parameters (K tr , mean transit time and K a ) were found to have high inter-individual variability. Keywords Rifampicin, population pharmacokinetics, pulmonary tuberculosis. References [1] Christian Lienhardt et al, Target regimen profiles for treatment of tuberculosis: a WHO document (2017). [2] J.G. Pasipanodya et al, Serum drug concentrations predictive of pulmonary tuberculosis outcomes, The Journal of infectious diseases 208(9) (2013) 1464-1473. https://doi.org/10.1093/infdis/jit352 [3] Jonathan Reynolds, Scott K Heysell (2014), Understanding pharmacokinetics to improve tuberculosis treatment outcome, Expert opinion on drug metabolism & toxicology 10(6) (2014) 813-823. https://doi.org/10.1517/17425255.2014.895813 [4] E.F. Egelund, A.B. Barth, C.A. Peloquin (2011), Population pharmacokinetics and its role in anti-tuberculosis drug development and optimization of treatment, Current pharmaceutical design 17(27) (2017) 2889-2899. https://doi.org/10.2174/138161211797470246. [5] J.F. Murray, D.E. Schraufnagel, P.C. Hopewell, Treatment of tuberculosis. A historical perspective, Annals of the American Thoracic Society 12(12) (2015) 1749-1759. https://doi.org/10.1513/AnnalsATS.201509-632PS [6] K.E. Stott, et al, Pharmacokinetics of rifampicin in adult TB patients and healthy volunteers: a systematic review and meta-analysis, Journal of Antimicrobial Chemotherapy 73(9) (2018) 2305-2313. https://doi.org/10.1093/jac/dky152. [7] Le Thi Luyen, Ta Manh Hung et al, Simultaneous Determination of Pyrazinamide, Rifampicin, Ethambutol, Isoniazid and Acetyl Isoniazid in Human Plasma by LC-MS/MS Method, Journal of Applied Pharmaceutical Science 8(09) (2018) 061-073. https://doi.org/ 10.7324/JAPS.2018.8910. [8] M.T. Chirehwa et al, Model-based evaluation of higher doses of rifampin using a semimechanistic model incorporating autoinduction and saturation of hepatic extraction, Antimicrobial agents and chemotherapy 60(1) (2016) 487-494. https://doi.org/10.1128/AAC.01830-15. [9] Paolo Denti et al, A population pharmacokinetic model for rifampicin auto-induction, The 3rd international workshop on clinical pharmacology of TB drugs (2010). [10] Y. Jing et al, Population pharmacokinetics of rifampicin in Chinese patients with pulmonary tuberculosis, The Journal of Clinical Pharmacology 56(5) (2016) 622-627. https://doi.org/10.1002/jcph.643. [11] S.R.C. Milán et al, Population pharmacokinetics of rifampicin in Mexican patients with tuberculosis, Journal of clinical pharmacy and therapeutics 38(1) (2013) 56-61. https://doi.org/10.1111/jcpt.12016. [12] Anushka Naidoo et al, Effects of genetic variability on rifampicin and isoniazid pharmacokinetics in South African patients with recurrent tuberculosis, Pharmacogenomics(00) (2013). https://doi.org/10.2217/pgs-2018-0166. [13] Neesha Rockwood et al, HIV-1 coinfection does not reduce exposure to rifampin, isoniazid, and pyrazinamide in South African tuberculosis outpatients, Antimicrobial agents and chemotherapy 60(10) (2016) 6050-6059. https://doi.org/10.1128/AAC.00480-16. [14] Alessandro Schipani et al, A simultaneous population pharmacokinetic analysis of rifampicin in Malawian adults and children, British Journal of Clinical Pharmacology 81(4) (2016) 679-687. https://doi.org/10.1111/bcp.12848. [15] Kok-Yong Seng et al, Population pharmacokinetics of rifampicin and 25-deacetyl-rifampicin in healthy Asian adults, Journal of Antimicrobial Chemotherapy 70(12) (2015) 3298-3306. https://doi.org/10.1093/jac/dkv268. [16] J.J. Wilkins et al, Population pharmacokinetics of rifampin in pulmonary tuberculosis patients, including a semimechanistic model to describe variable absorption, Antimicrobial agents and chemotherapy 52(6) (2008)2138-2148. https://dx.doi.org/10.1128%2FAAC.00461-07. [17] Sylvain Goutelle et al, Population modeling and Monte Carlo simulation study of the pharmacokinetics and antituberculosis pharmacodynamics of rifampin in lungs, Antimicrobial agents and chemotherapy 53(7) (2009) 2974-2981. https://doi.org/10.1128/AAC.01520-08. [18] R.M. Savic et al, Implementation of a transit compartment model for describing drug absorption in pharmacokinetic studies, Journal of pharmacokinetics and pharmacodynamics 34(5) (2007) 711-726. https://doi.org/10.1007/s10928-007-9066-0. [19] B.J. Anderson, N.H.G. Holford, Mechanism-based concepts of size and maturity in pharmacokinetics, Annu. Rev. Pharmacol. Toxicol 48 (2008) 303-332. https://doi.org/10.1146/annurev.pharmtox.48.113006.094708. [20] Kok-Yong Seng et al, Population pharmacokinetic analysis of isoniazid, acetyl-isoniazid and isonicotinic acid in healthy volunteers, Antimicrobial agents and chemotherapy, pp. AAC. (2015) 01244-15. https://doi.org/10.1128/AAC.01244-15. [21] Sarayut Janmahasatian et al, Quantification of lean bodyweight, Clinical pharmacokinetics 44(10), (2005) 1051-1065. https://doi.org/10.2165/00003088-200544100-00004. [22] Kidola Jeremiah et al, Nutritional supplementation increases rifampin exposure among tuberculosis patients coinfected with HIV, Antimicrobial agents and chemotherapy 58(6) (2014) 3468-3474. https://doi.org/10.1128/AAC.02307-13